2018
DOI: 10.7705/biomedica.v38i4.4042
|View full text |Cite
|
Sign up to set email alerts
|

First report of Dioctophyma renale (Nematoda, Dioctophymatidae) in Colombia

Abstract: La dioctofimosis es una enfermedad parasitaria zoonótica causada por Dioctophyma renale (Goeze, 1782), de amplia distribución mundial, que afecta a un gran número de mamíferos silvestres y domésticos.Se reporta el primer caso de dioctofimosis canina en Colombia. El animal fue encontrado muerto en las calles del municipio de Yondó, Antioquia. Su cadáver fue llevado al Instituto Universitario de la Paz (UNIPAZ) donde se practicó la necropsia.En el riñón derecho se encontró un parásito, el cual fue enviado al Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Brazil is the country with the highest number of reported D. renale cases in domestic dogs with prevalence rates up to 14.2% (Ferreira et al, 2010;Nakagawa et al, 2007;Pedrassani et al, 2017;Rappeti et al, 2017). Canine dioctophymatosis has also been reported recently in other Latin America countries, such as Colombia (Florez et al, 2018) and Argentina (Radman et al, 2017). Recent studies have also reported D. renale in dogs in Iran (Vafae Eslahi et al, 2017;Zolhavarieh et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Brazil is the country with the highest number of reported D. renale cases in domestic dogs with prevalence rates up to 14.2% (Ferreira et al, 2010;Nakagawa et al, 2007;Pedrassani et al, 2017;Rappeti et al, 2017). Canine dioctophymatosis has also been reported recently in other Latin America countries, such as Colombia (Florez et al, 2018) and Argentina (Radman et al, 2017). Recent studies have also reported D. renale in dogs in Iran (Vafae Eslahi et al, 2017;Zolhavarieh et al, 2016).…”
Section: Discussionmentioning
confidence: 97%